2019
DOI: 10.1002/iju5.12090
|View full text |Cite
|
Sign up to set email alerts
|

Primary male urethral squamous cell carcinoma presenting with a genital abscess

Abstract: Abbreviations & Acronyms BSC = best supportive care Cx = chemotherapy nd = not described Rx = radiation therapy Correspondence: Hiroya

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The authors reported each 1 case of SCC associated with abscess or fistula (Chandramohan et al 2010 ; Jamieson and Goode 1982 ; Seya et al 2007 ; Moore et al 2016 ; Creta et al 2017 ; Garg et al 2018 ; Mizusawa et al 2019 ). In the majority of the cases, the patients were male (5/7), only 1 was female, and in 1 case, the sex was not reported.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors reported each 1 case of SCC associated with abscess or fistula (Chandramohan et al 2010 ; Jamieson and Goode 1982 ; Seya et al 2007 ; Moore et al 2016 ; Creta et al 2017 ; Garg et al 2018 ; Mizusawa et al 2019 ). In the majority of the cases, the patients were male (5/7), only 1 was female, and in 1 case, the sex was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…In one patient, the abscess was located in the gluteal region (Chandramohan et al 2010 ). In the remaining 4 case reports, the infection was found in the perineal region followed by the delayed diagnosis of a urethral tumour (3 cases) (Moore et al 2016 ; Garg et al 2018 ; Mizusawa et al 2019 ) or a carcinoma of unknown primary origin (CUP) (Creta et al 2017 ) (delay of 2–18 months).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations